Architecture, futurability and the untimely : on the unpredictability of the past - Mayrhofer, Ingrid, 1954-; Mayrhofer, Ingrid, 1954-; Bettum, Johan; Bühlmann, Vera; Ennemoser, Benjamin; Forster, Kurt W.; Han, Eugene; Kolatan, Ferda; Luarasi, Skender; Mergold, Aleksandr; Ozvaldič, Maja; Paolo Tamburelli, Pier; et al. (Architekturen (Bielefeld, Germany), 2022)
The planetary instantaneity that digital technologies have enabled is leading to an effacement of the divisions that separate the past from the future, ensuring that the present is ubiquitous. While contemporary architecture seems to have lost the capacity to conceive of the past as a transformative force, this book stresses the need to rethink today's complex temporal mechanisms through the notion of the untimely. This concept opens up a whole spectrum of possibilities to go beyond what seems predictable. The contributors to this book employ critical concepts and architectural design tools in order to offer experimental and speculative approaches for unknown futures of architecture.